Influence of bias voltage on the optical and structural properties of nc-Si:H films grown by layer-by-layer (LBL) deposition technique - Tong, G.B.; Gani, S.M.A.; Muhamad, M.R.; Rahman, S.A. (2009)
The effects of applying a positive bias of 25 to 100 V on the optical, structural and photoluminescence (PL) properties of hydrogenated nanocrystalline silicon (nc-Si:H) films produced by layer-by-layer (LBL) deposition technique has been studied. Optical characterization of the films has been obtained from UV-VIS-NIR spectroscopy measurements. Structural characterization has been performed using X-ray diffraction, micro-Raman spectroscopy and field emission scanning electron microscope (FESEM). PL spectroscopy technique has been used to investigate the PL properties of the films. In general, the films formed shows a mixed phase of silicon (Si) nanocrystallites embedded within an amorphous phase of the Si matrix. The crystalline volume fraction and grain size of the Si nanocrystallites have been shown to be strongly dependent on the applied bias voltage. High applied bias voltage enhances the growth rate of the films but reduces the refractive index and the optical energy gap of the films. Higher crystalline volume fraction of the films prepared at low bias voltages exhibits room temperature PL at around 1.8 eV (700 nm). (c) 2009 Elsevier B.V. All rights reserved.